2017
DOI: 10.1002/sdtp.11860
|View full text |Cite
|
Sign up to set email alerts
|

P‐10: High‐Density Plasma Sputtered InZnSnO Thin‐Film Transistors Fabricated by Back Channel Etching Method on Flexible Polyimide Substrate

Abstract: We demonstrate the fabrication of high performance InZnSnO thinfilm transistors (TFT) with the field-effect mobility of 25 cm 2 /Vs on about 10 um-thin polyimide substrate. Back-channel etch (BCE) process in the bottom gate configuration is employed for easy implementation of devices with shorter channel length and smaller parasitic capacitance and cost-effective fabrication compared with devices with etch-stop layer (ESL). For highly uniform electrical characteristics with high field-effect mobility, InZnSnO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, the excimer laser process is expensive and fine laser energy control is required because the plastic substrate can be damaged by thermal energy. Cho et al reported that In-Sn-Zn-O (ITZO) TFTs were fabricated on PI substrates [80]. During the delamination process, they used an excimer laser.…”
Section: Flexible Substrates and The Delamination Processmentioning
confidence: 99%
“…However, the excimer laser process is expensive and fine laser energy control is required because the plastic substrate can be damaged by thermal energy. Cho et al reported that In-Sn-Zn-O (ITZO) TFTs were fabricated on PI substrates [80]. During the delamination process, they used an excimer laser.…”
Section: Flexible Substrates and The Delamination Processmentioning
confidence: 99%